Induced resistance to Fusarium wilt of banana by exogenous applications of indoleacetic acid - Fernández-Falcón, Marino; Borges, Andres; Borges-Pérez, Andres (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2003)
Fusarium wilt of banana (Panama disease), caused by Fusarium oxysporum f.sp. cubense, is a soilborne systemic disease which occludes host vascular system. We report here two experiments on resistance induction with banana plants (cv. Dwarf Cavendish) carried out in glass greenhouse with different indoleacetic acid treatments, which are capable of inducing resistance to Panama disease. The results obtained in these experiments suggest that the exogenous application of indoleacetic acid to banana plants induce resistance to Panama disease and that the resistance induction is more effective when performed using low doses and frequent applications. This work seems to confirm the role played by indoleacetic acid according to Beckman’s models as, one of the major defence factors of the host plant in vascular wilt diseases.